In vitro assessment of Moringa Oleifera leaf extract’s protective impact on fibroblast cell line (WI-38) exposed to electronic cigarette liquid - Raneem F. Obeid; Yara Y. Mouselhy; Mona Eltaher; Radwa T. El-sharkawy (Scientific Reports)
Abstract Moringa oleifera (MO), a medicinal herb, has been studied in recent decades for its diverse range of biological activities. Several studies have revealed that MO leaf extract (MOLE) possesses cytoprotective properties, while other studies have reported anti-proliferative potential. This study was conducted to assess the potential effect of MOLE on electronic cigarette liquid (EC e-liquid) treated human lung fibroblast cell line (WI-38). An MTT assay was performed to investigate the potential effect of EC e-liquid and MOLE on cell viability and determine the cytotoxic concentration (CC50) in WI-38 cells. Cells were treated with 190.2 µg/mL of EC e-liquid (EC group) and 33.2 µg/mL of EC e-liquid and MOLE (EC + MOLE group) for 24 h. Analysis of apoptosis and cell cycle was performed using flow cytometric assay. Moreover, the expression of apoptosis-related proteins Bax and Bcl2 was measured using ELISA.Our findings revealed that MOLE demonstrated a cytotoxic effect on EC e-liquid treated WI-38 cells through induction of apoptosis via up-regulation of Bax and down-regulation of Bcl2. Additionally, MOLE induced cell cycle arrest at the S phase. Overall, these findings indicate that MOLE is an inefficient cytoprotective agent against EC e-liquid cytotoxicity; nonetheless, it exerts a cytotoxic effect, suggesting a promising role as a valuable anti-proliferative agent.